OPTIMIZED CHEMICAL SYNTHESIS OF STABLE SILVER NANOPARTICLES USING VARIOUS REDUCING AND STABILIZING AGENTS - Hoshimov, Farhod; Lutpillayeva, Masuda (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article discusses the influence of stabilizing agents on the stability and particle size of silver nanoparticles (AgNPs) during synthesis. AgNPs were synthesized via chemical reduction of silver nitrate (AgNO₃) using different reducing agents (sodium citrate, hydrazine, glucose) and stabilizers (gelatin, dextrin, and PVP). Syntheses were conducted under various temperature conditions (0°C, 20°C, 40°C), and the particle size of the resulting nanoparticles was measured using the MasterSizer-3000 laser diffraction method. The most stable AgNPs were obtained using sodium citrate as a reducing agent and 1% gelatin as a stabilizer at 20°C. Under these conditions, the synthesized particles exhibited small and uniform size and remained stable for up to 6 months without sedimentation. Increasing the temperature led to the formation of larger particles. Sodium citrate and gelatin represent an optimal combination for the controlled and stable synthesis of AgNPs. This approach offers promising applications in medicine, biotechnology, and environmental sciences.